Effect of a Good Oral - Dental Care Protocol on Inflammation and Oral Lesions in Renal Transplant Patients: A Randomized Control Study. (July 2018) - Sharma, Lokesh; Sharma, Raj Kumar; Reddy, Vamsi K; Singh, Sanjay; Mehrotra, Sonia; Gupta, Amit; Prasad, Narayan; Bhadauria, Dharmendra S.; Kaul, Anupama; Patel, Manas R.
Abstract : N/A: Inflammation plays an important role in causing complications in CKD and transplant patients. C-reactive protein and pro-inflammatory cytokines could predict outcomes in transplant patient. Poor oral health results in inflammation and cytokine production. There is need to evaluate the benefit of good oral hygiene on renal transplant outcome. A randomized controlled trial was carried out amongst CKD patients going for renal transplantation. The randomization was done in 100 CKD patients going for transplantation. All patients had dental and oral examination (Type III clinical examination as per American Dental Association specifications and WHO oral health proforma, 2013) Group I (Non interventional group) 50 patients. Group II (Intervention group) - 50 patients of chronic kidney disease going for transplantation. Group III (Control group) comprised of 50 healthy age, sex matched subjects. Intervention group followed regular tooth brushing, use of dental floss along with use of mouth wash twice every day and counseling sessions for good oral and dental care for a period of 3 months after transplant. Non-intervention group continued usual oral and dental care. Both groups had base line oral examination just before transplantation and at 3 months after transplant. The oral and dental findings specially the periodontitis score was compared between groups I and II and with the healthy controls. CRP (C- reactive protein) values were assayed at baseline and after 3 months. Comparison of CRP values between Interventional and non-interventional groups at baseline and at 3months showed that periodontitis score and CRP significantly came down at 3 months in intervention group as compared to non- intervention group . CRP values in the interventional and non-intervention groups were analyzed in relation to presence of donor specific antibodies (DSA) and HLA mismatch scores in the two groups. Our data shows that after aggressive dental and mouth hygiene routine, intervention group patients showed significant decline in CRP values as compared to the non intervention group. It almost reached close to values in normal controls. This was seen in both patient groups with less than and more than 3-HLA mis-matches. In patients with DSA at time of transplantation, base line CRP values were significantly higher as compared to those with no DSA, but CRP values even in DSA positive group came down significantly with aggressive dental and mouth care routine at 3 months after transplantation Figure. No caption available. This is a report of results of a randomized control study in transplant recipients showing the benefits of good oral and dental care in relation to inflammation, DSA and HLA mis-matches. The present study concludes that the oral hygiene of the patients with chronic kidney disease going for transplant is deteriorated. Good oral and dental care in transplant recipients can improve inflammation which could have beneficial effect on post transplant outcomes.